DETERMINASI KINERJA PENGAWAS PEMILU PROVINSI SULAWESI SELATAN MELALUI KOMITMEN KERJA: PENDEKATAN STRUCTURAL EQUATION MODEL - Zulkifli Sultan (Departemen Manajemen, 2022)
The purpose of this study is to analyze and explain the impact of regulation and work motivation on the performance of election administrators in South Sulawesi through work commitment interventions. The approach used is a quantitative approach using data sources obtained from the South Sulawesi Election Supervisory Agency office. Questionnaires were distributed to 140 respondents from a total population of 140 employees using a saturated sample. The data analysis used in this research is a quantitative analysis using SEM (Structural Equation Modeling) or structural equation modeling using the AMOS program. This test is expected to obtain new information about the relationship between the independent and dependent variables by developing some statistics and the existence of intervening variables. Based on statistical calculations, regulation has a significant effect on KPU performance, and motivation has an insignificant effect on KPU performance. In addition, work commitment has an influence, but not significantly, on the performance of election administrators. In addition, regulatory variables have a large, but not significant, impact on work commitment. The variable of work motivation has a significant effect on work commitment. The results of the tests carried out by the results of statistical tests using the Sobel test calculator have a significant but not significant effect on the regulation of election performance mediated by work commitment. On the other hand, work motivation on the performance of election administrators is influential but not significantly mediated by work commitment